Pilot clinical trial of macimorelin to assess safety and efficacy in patients with cancer cachexia. Issue 2 (1st March 2023) - Herodes, Megan; Anderson, Lindsey J.; Shober, Samuel; Schur, Ellen A.; Graf, Solomon A.; Ammer, Nicola; Salas, Ramiro; Marcelli, Marco; Garcia, Jose M.
Abstract: Background: Cancer cachexia is associated with reduced body weight, appetite and quality of life (QOL) with no approved treatments. Growth hormone secretagogues like macimorelin have potential to mitigate these effects. Methods: This pilot study assessed the safety and efficacy of macimorelin for 1 week. Efficacy was defined a priori as 1‐week change in body weight (≥0.8 kg), plasma insulin‐like growth factor (IGF)‐1 (≥50 ng/mL) or QOL (≥15%). Secondary outcomes included food intake, appetite, functional performance, energy expenditure and safety laboratory parameters. Patients with cancer cachexia were randomized to 0.5 or 1.0 mg/kg macimorelin or placebo; outcomes were assessed non‐parametrically. Results: Participants receiving at least one of either macimorelin dose were combined ( N  = 10; 100% male; median age = 65.50 ± 2.12) and compared with placebo ( N  = 5; 80% male; median age = 68.00 ± 6.19). Efficacy criteria achieved: body weight (macimorelin N  = 2; placebo N  = 0; P  = 0.92); IGF‐1 (macimorelin N  = 0; placebo N  = 0); QOL by Anderson Symptom Assessment Scale (macimorelin N  = 4; placebo N  = 1; P  = 1.00) or Functional Assessment of Chronic Illness Therapy‐Fatigue (FACIT‐F; macimorelin N  = 3; placebo N  = 0; P  = 0.50). No related serious or non‐serious adverse events were reported. In macimorelin recipients, change in FACIT‐F was directly associated with change in body weight ( r  = 0.92, P  = 0.001), IGF‐1 ( r  = 0.80, P  = 0.01), and caloric intake ( r  = 0.83, P  = 0.005), and inversely associated with change in energy expenditure ( r  = −0.67, P  = 0.05). Conclusions: Daily oral macimorelin for 1 week was safe and numerically improved body weight and QOL in patients with cancer cachexia compared with placebo. Longer term administration should be evaluated for mitigation of cancer‐induced reductions in body weight, appetite and QOL in larger studies.